2020
DOI: 10.3389/fcvm.2020.542485
|View full text |Cite|
|
Sign up to set email alerts
|

p90RSK-MAGI1 Module Controls Endothelial Permeability by Post-translational Modifications of MAGI1 and Hippo Pathway

Abstract: Previously, we reported that post-translational modifications (PTMs) of MAGI1, including S741 phosphorylation and K931 de-SUMOylation, both of which are regulated by p90RSK activation, lead to endothelial cell (EC) activation. However, roles for p90RSK and MAGI1-PTMs in regulating EC permeability remain unclear despite MAGI1 being a junctional molecule. Here, we show that thrombin (Thb)-induced EC permeability, detected by the electric cell-substrate impedance sensing (ECIS) based system, was decreased by over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…In addition to its role as regulator of EC activation, MAGI1-large tumor suppressor kinases (LATS) 1/2-YAP interaction was shown to modulate endothelial permeability. Couzens and Weiss et al found that MAGI1 is one of the binding partners of the LATS1 [82], and Abe et al discovered that MAGI1 inhibits LATS1/2 expression, maintaining the EC barrier function by regulating the Hippo pathway [83]. In their study, they show that MAGI1 regulates LATS1 and 2 expression transcriptionally, and MAGI-mediated reduction of LATS1 and 2 expression leads to increased YAP activation, which is critically involved in the maintenance of EC barrier function (i.e., inhibition of EC permeability).…”
Section: Magi1 Vascular Functionsmentioning
confidence: 99%
“…In addition to its role as regulator of EC activation, MAGI1-large tumor suppressor kinases (LATS) 1/2-YAP interaction was shown to modulate endothelial permeability. Couzens and Weiss et al found that MAGI1 is one of the binding partners of the LATS1 [82], and Abe et al discovered that MAGI1 inhibits LATS1/2 expression, maintaining the EC barrier function by regulating the Hippo pathway [83]. In their study, they show that MAGI1 regulates LATS1 and 2 expression transcriptionally, and MAGI-mediated reduction of LATS1 and 2 expression leads to increased YAP activation, which is critically involved in the maintenance of EC barrier function (i.e., inhibition of EC permeability).…”
Section: Magi1 Vascular Functionsmentioning
confidence: 99%
“…Nevertheless, the regulation of YAP1 by MAGIs is seemingly complex. Accordingly, in endothelial cells, MAGI1 depletion markedly increases LATS1/2 at mRNA and protein levels leading to a reduction in YAP expression and endothelial permeability [ 106 ].…”
Section: Implication Of Magi Molecular Scaffolds In the Control Of Carcinogenesismentioning
confidence: 99%
“…MAGI1 proves also to be a target of caspase-3 and -7 during the apoptotic process, MAGI1 cleavage contributes to cell junction disassembly, a key feature of apoptosis [ 103 ]. In endothelial cells, thrombin stimulates p90RSK that directly phosphorylates MAGI1 at Serine 741 and induces MAGI1 deSUMOylation at Lysine 931, the consecutive release of MAGI1 from adherens and tight junctions leading to endothelial permeability [ 106 ]. In this model, this effect was mimicked by MAGI1 down-regulation.…”
Section: Implication Of Magi Molecular Scaffolds In the Control Of Carcinogenesismentioning
confidence: 99%
“…The effect of increased permeability by thrombin has been shown, and thrombin-induced permeability (TIP) is a well-characterized and widely used barrier-disruptive effect used in a permeability model in endothelial cells (ECs) ( Li et al, 2019 ; Abe et al, 2020 ). Thrombin affects cell morphology and intracellular contraction by reorganization of the cytoskeleton ( Amerongen et al, 2000 ) and thus enhances EC paracellular permeability.…”
Section: Introductionmentioning
confidence: 99%